1996
DOI: 10.1093/infdis/173.2.418
|View full text |Cite
|
Sign up to set email alerts
|

The Broad-Spectrum Activity and Efficacy of Catheters Coated with Minocycline and Rifampin

Abstract: The in vitro and in vivo activities of catheters coated with minocycline and rifampin and with chlorhexidine gluconate and silver sulfadiazine were evaluated. When incubated in serum at 37 degrees C, the half-life of the inhibitory activity of catheters coated with minocycline and rifampin was 25 days compared with 3 days for catheters coated with chlorhexidine gluconate and silver sulfadiazine. In a rabbit model, catheters coated with minocycline and rifampin were significantly more efficacious than catheters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
115
2
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(124 citation statements)
references
References 33 publications
3
115
2
2
Order By: Relevance
“…However, in vitro data indicate that these impregnated catheters could increase the incidence of minocycline and rifampin resistance among pathogens, especially staphylococci. The half-life of antimicrobial activity against S. epidermidis is 25 days with catheters coated with minocycline/rifampin, compared with 3 days for the first-generation catheters coated with chlorhexidine/silver sulfadiazine in vitro [87]. In vivo, the duration of antimicrobial activity of the minocycline/rifampin catheter is longer than that of the first-generation chlorhexidine/silver sulfadiazine catheter [91].…”
Section: Antimicrobial/antiseptic Impregnated Catheters and Cuffsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in vitro data indicate that these impregnated catheters could increase the incidence of minocycline and rifampin resistance among pathogens, especially staphylococci. The half-life of antimicrobial activity against S. epidermidis is 25 days with catheters coated with minocycline/rifampin, compared with 3 days for the first-generation catheters coated with chlorhexidine/silver sulfadiazine in vitro [87]. In vivo, the duration of antimicrobial activity of the minocycline/rifampin catheter is longer than that of the first-generation chlorhexidine/silver sulfadiazine catheter [91].…”
Section: Antimicrobial/antiseptic Impregnated Catheters and Cuffsmentioning
confidence: 99%
“…The mean duration of catheter placement in one metaanalysis ranged from 5.1 to 11.2 days [86]. The half-life of antimicrobial activity against S. epidermidis is 3 days in vitro for catheters coated with chlorhexidine/silver sulfadiazine; this antimicrobial activity decreases over time [87]. The benefit for the patients who receive these catheters will be realized within the first 14 days [86].…”
Section: Antimicrobial/antiseptic Impregnated Catheters and Cuffsmentioning
confidence: 99%
“…In the last decade, several strategies to control biofilm growth on medical devices have been suggested, including the use of topical antimicrobial ointments, minimizing the length of time of catheterization, using catheters provided with a surgically implanted cuff (9), and coating the catheter lumen with antimicrobial agents (1,6,23,24,25,29,30,32,39). Existing antimicrobial-loaded catheters suffer from a number of limitations, including the rapid release of the adsorbed antibiotic in the first hours after implantation and, as a result, a relatively short persistence of antibacterial action (7).…”
mentioning
confidence: 99%
“…Raad et al 28 found that the rifampin-minocycline combination also displayed broad-spectrum inhibitory activity against Gram-negative bacteria and yeast cells. Raad et al 29 suggested that an advantage of the combination of minocycline and rifampin is that they are not used as primary agents in the treatment of systemic infections.…”
Section: Infection Preventionmentioning
confidence: 99%
“…29 In subsequent clinical studies with central venous catheters, Raad et al 30 found that rifampin-minocycline-coated catheters significantly reduced the risk for catheter-related colonization and bloodstream infections. Bacterial colonization occurred with 26% of uncoated catheters compared with 8% of catheters coated with minocycline and rifampin (Po0.01).…”
Section: Infection Preventionmentioning
confidence: 99%